Case Report: Radioactive Holmium-166 Microspheres for the Intratumoral Treatment of a Canine Pituitary Tumor - Morsink, Nino Chiron; Klaassen, Nienke Johanna Maria; Meij, Björn Petrus; Kirpensteijn, Jolle; Grinwis, Guillaume Cornelis Maria; Schaafsma, Irene Afra; Hesselink, Jan Willem; Nijsen, Johannes Frank Wilhelmus; van Nimwegen, Sebastiaan Alexander (Frontiers in Veterinary Science, 2021)
Introduction: In this case study, a client-owned dog with a large pituitary tumor was experimentally treated by intratumoral injection of radioactive holmium-166 microspheres (166HoMS), named 166HoMS microbrachytherapy. To our knowledge, this is the first intracranial intratumoral treatment through needle injection of radioactive microspheres. Materials and methods: A 10-year-old Jack Russell Terrier was referred to the Clinic for Companion Animal Health (Faculty of Veterinary Medicine, Utrecht University, The Netherlands) with behavioral changes, restlessness, stiff gait, and compulsive circling. MRI and CT showed a pituitary tumor with basisphenoid bone invasion and marked mass effect. The tumor measured 8.8 cm3 with a pituitary height-to-brain area (P/B) ratio of 1.86 (pituitary height (cm) · 10 / brain area (cm2)). To reduce tumor volume and neurological signs, 166HoMS were administered in the tumor center by transsphenoidal CT-guided needle injections. Results: Two manual CT-guided injections were performed containing 0.6 ml of 166HoMS suspension in total. 1097 MBq was delivered resulting in a mean calculated tumor dose of 1866 Gy. At 138 days after treatment, the tumor volume measured 5.3 cm3 with a P/B ratio of 1.41 cm-1, revealing a total tumor volume reduction of 40%. Debulking surgery was performed five months after 166HoMS treatment due to recurrent neurological signs. The patient was euthanized two weeks later at request of the owners. Histopathological analysis indicated a pituitary adenoma at time of treatment, with more malignant characteristics during debulking surgery. Conclusion: The 40% tumor volume reduction without evident severe periprocedural side effects demonstrated the feasibility of intracranial intratumoral 166HoMS treatment in this single dog.